A Posteriori Error Analysis of the FEM Solution for Generic Linear Second-Order ODEs - Wahran Shaker; Mohammad Sabawi (Academic Science Journal, 2024)
In this paper, a posteriori error analysis has been examined and investigated for the continuous (conforming) Galerkin finite element method used for solving a general scalar linear second-order ordinary BVPs.